2000
DOI: 10.1002/(sici)1097-4628(20000307)75:10<1288::aid-app10>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR characterization of cyclomaltoheptaose (?-cyclodextrin) polymers using high-resolution magic angle spinning with gradients

Abstract: Solid-state nuclear magnetic resonance (NMR) techniques were used to characterize cyclomaltoheptaose (␤-cyclodextrin, ␤-CD) polymers. These insoluble materials have been investigated by cross-polarization magic angle spinning with dipolar decoupling (CP/MAS), magic angle spinning without dipolar decoupling (MAS), and high-resolution magic angle spinning with gradients (HRMAS). These NMR spectra allow the assignment of the principal 1 H and 13 C signals. The presence of two distinct components (cross-linked ␤-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 44 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…[30,31] Other HR-MAS studies observed the impact of cross-linking in solvent swollen poly(amidoamine) polymers, the nature of water interactions in these same class of polymers, [32,33] or the cross-linking performance in silicon-containing soybean-oil copolymers. [34] HR-MAS NMR has also been used to study the functionalization of poly hydroxyethyl methacrylate (HEMA) cryogels, [35] cyclomaltoheptaose polymers, [36] the synthesis of hyper-branched bis (hydroxymethyl) propionic acid (bis-MPA) polymers as a function of catalysts, [37] and polymers for nanoparticle stabilization. [38] HR-MAS NMR has found use in investigation of porous polyalkylvinyl ether polymer particles being used for stationary phases in chromatographic applications.…”
Section: Polymersmentioning
confidence: 99%
“…[30,31] Other HR-MAS studies observed the impact of cross-linking in solvent swollen poly(amidoamine) polymers, the nature of water interactions in these same class of polymers, [32,33] or the cross-linking performance in silicon-containing soybean-oil copolymers. [34] HR-MAS NMR has also been used to study the functionalization of poly hydroxyethyl methacrylate (HEMA) cryogels, [35] cyclomaltoheptaose polymers, [36] the synthesis of hyper-branched bis (hydroxymethyl) propionic acid (bis-MPA) polymers as a function of catalysts, [37] and polymers for nanoparticle stabilization. [38] HR-MAS NMR has found use in investigation of porous polyalkylvinyl ether polymer particles being used for stationary phases in chromatographic applications.…”
Section: Polymersmentioning
confidence: 99%
“…In particular, the selective properties of CDs and their derivatives can be employed in all chromatographic techniques for the separation of structural, geometric, and optical isomers. They are used in HPLC [43, 44, 124 -127], TLC [42,128], GC [43, 45, 129 -131], affinity chromatography [132,133], ion-exclusion chromatography [134], preparative chromatography [135], electrophoresis [39,48,136,137] and micellar electrokinetic chromatography [40,138]. They were employed successfully as selective components in the mobile phase and as stationary phase.…”
Section: Inclusion Propertiesmentioning
confidence: 99%
“…In the literature, there have been numerous studies on the preparation [139 -152, 167 -176, 191 -198, 206 -217], characterization [19,40,140,149,152,184], properties [149 -152, 158], and applications [17 -20, 153 -200, 206 -217] of water insoluble materials containing CD molecules. There are several reported procedures for synthesizing these adsorbents and the methods can be generally classified in two ways.…”
Section: Adsorbents Containing Cyclodextrinsmentioning
confidence: 99%
See 2 more Smart Citations